2017
DOI: 10.18632/oncotarget.15657
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation of progesterone receptor in breast cancer

Abstract: Hormone receptor status is of significant value when deciding on anti-estrogenic adjuvant therapy for breast cancer tumors. However, while estrogen receptor (ER) regulation was intensively studied, the regulation of progesterone receptor (PR) levels has not been extensively investigated. MicroRNAs (miRNAs, miRs) are post-transcriptional negative regulators of gene expression involved in diverse cellular processes. The aim of this study was to identify miRNAs that regulate PR in breast cancer.We mapped potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
2
17
1
Order By: Relevance
“…In the case of luminal breast cancer, our studies show that the ability of progesterone plus PR-A to prevent suppression of miR-26b-5p by estrogen leads to increased invasion and metastasis, again underscoring cell type-specific differences in the actions of miR-26b-5p. We note that in a recent report (46), the authors suggest that PR may be a target of miR-26b and suggest a negative correlation between miR-26b expression and total PR mRNA in breast tumors, whereas we have observed a positive correlation between miR-26b and the PR isoform A and regulatory effects consistent with a positive correlation. The functional studies reported (46), which were only performed in MCF-7 cells, only showed a modest decrease in PR mRNA (ϳ20%) upon ectopic overexpression of miR-26b (at an undetermined level), and the study did not measure PR protein or function and did not examine the effect of depleting endogenous miR-26b.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the case of luminal breast cancer, our studies show that the ability of progesterone plus PR-A to prevent suppression of miR-26b-5p by estrogen leads to increased invasion and metastasis, again underscoring cell type-specific differences in the actions of miR-26b-5p. We note that in a recent report (46), the authors suggest that PR may be a target of miR-26b and suggest a negative correlation between miR-26b expression and total PR mRNA in breast tumors, whereas we have observed a positive correlation between miR-26b and the PR isoform A and regulatory effects consistent with a positive correlation. The functional studies reported (46), which were only performed in MCF-7 cells, only showed a modest decrease in PR mRNA (ϳ20%) upon ectopic overexpression of miR-26b (at an undetermined level), and the study did not measure PR protein or function and did not examine the effect of depleting endogenous miR-26b.…”
Section: Discussionsupporting
confidence: 60%
“…We note that in a recent report (46), the authors suggest that PR may be a target of miR-26b and suggest a negative correlation between miR-26b expression and total PR mRNA in breast tumors, whereas we have observed a positive correlation between miR-26b and the PR isoform A and regulatory effects consistent with a positive correlation. The functional studies reported (46), which were only performed in MCF-7 cells, only showed a modest decrease in PR mRNA (ϳ20%) upon ectopic overexpression of miR-26b (at an undetermined level), and the study did not measure PR protein or function and did not examine the effect of depleting endogenous miR-26b. Additionally, the correlative analysis was performed using data from only 10 of 19 tumor specimens, and the arbitrary criteria for selecting this small sample subset were not unbiased.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, miRNAs have been shown to be involved in the development of many human diseases [22-25]. For example, miRNAs play essential roles in cancer progress [26, 27], cardiovascular diseases, kidney diseases and improper immune responses in macrophages [28-32]. Several miRNAs (e.g., miR-21, miR-29a, miR-30s, miR-146a, miR-192, miR-193, and miR-200) are exploited as important biomarkers of renal diseases [33-39].…”
Section: Mirna Biogenesis and Functionmentioning
confidence: 99%
“…In line with this, the lifespan of patients with low amounts of miR‐200c is significantly reduced because of the missing impact of miR‐200c on PR expression (Tuomarila et al, 2014; http://targetcan.org). Other miRNAs strongly connected to the downregulation of PR in breast cancer are miR‐23a, miR‐26b, miR‐129‐2, and miR‐181a (Gilam et al, ; Godbole et al, ). Since some of these miRNAs are already described as tumor suppressor factors known to target the classical PR (http://targetscan.org), the use of miRNA mimics could potentially lead to a decreased tumor cell invasion in PR‐positive breast cancer.…”
Section: Progesterone and Prsmentioning
confidence: 99%